MODERNITY AND THE PROBLEM OF ITS CHRISTIAN PAST: THE GEISTESGESCHICHTEN OF BLUMENBERG, BERGER, AND GAUCHET. Issue 2 (May 2016) - GRIFFIOEN, SJOERD
ABSTRACT: Recent years have seen the rise of "post‐secularism, " a new perspective that criticizes the dominant secularization narrative according to which "modernity" and "religion" are fundamentally antagonistic concepts. Jürgen Habermas, Charles Taylor, and Gianni Vattimo are the most prominent defenders of such a post‐secularist account. But though post‐secularism presents itself as a necessary rectification of the secularization story, it has not been able to come up with a credible and generally accepted alternative account. In this article I will explain why, arguing that the use of "essentially contested concepts" such as "Christianity" and "modernity" rest on normative standpoints of the narrators that are incompatible with one another. To show this I will analyze the position of three older voices in the debate, namely those of Hans Blumenberg, Peter Berger, and Marcel Gauchet. These authors seem to agree in understanding the modern disenchanted worldview in relation to Christian transcendence, but I will show that beneath their similar narratives lie incompatible normative beliefs on which their use of the concepts of "Christianity" and "modernity" is founded. After having laid bare the roots of the contemporary debate by exploring these three fundamental positions, I will finally argue that we should not take their accounts as objective, historical descriptions but as what Richard Rorty has called " Geistesgeschichte ": a speculative history that is aimed at conveying a moral, in which essentially contested concepts play a constitutive role. Each author draws his own moral, and consequently each author will construct his own corresponding history. This lesson can then be applied to the contemporary debate on secularization. The value of the debate does not lie in its historical claims but in the visions of the protagonists; at the end of this article I will explain how we can capitalize on this value.